Pressure-sensitive adhesive and pressure-sensitive adhesive sheet
A thermoplastic block copolymer and resin combination addresses the challenge of high biomass adhesives by ensuring excellent adhesion and cohesion, overcoming previous adhesive performance issues.
Patent Information
- Application Number
- JP2024095862
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-06-13
- Publication Date
- 2025-01-24
AI Technical Summary
Existing adhesives face challenges in achieving high biomass content while maintaining sufficient adhesion and cohesion, particularly with acrylic adhesives having long-chain alkyl groups and natural resin content, leading to issues with peeling and adhesive performance.
A thermoplastic block copolymer and resin combination, comprising a copolymer between monovinyl hydrocarbons and diene compounds, with specific ratios of styrene-based block copolymers and rosin-based resins, along with optional plasticizers, to create an adhesive with a biomass level of 60% or more, ensuring excellent adhesion and cohesion.
The solution provides adhesives with high biomass content that exhibit superior adhesive characteristics, including strong adhesion, cohesion, and performance on curved surfaces, while avoiding the limitations of previous technologies.
Smart Images

Figure 2025013190000001
Abstract
Description
[Technical field]
[0001] An embodiment of the present invention relates to a pressure-sensitive adhesive having a biomass ratio of 60% or more, comprising a thermoplastic block copolymer (X) that is a copolymer of a monovinyl aromatic hydrocarbon and a conjugated diene compound, and a tackifier resin (Y). The present invention also relates to a pressure-sensitive adhesive sheet having a pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive. [Background technology]
[0002] Adhesive sheets having an adhesive layer formed from an adhesive are easy to handle and are therefore used in a wide range of fields as labels, tapes and adhesive applications. For example, synthetic rubber-based adhesives, which are made by blending a tackifier resin such as a petroleum-based resin with a thermoplastic block copolymer such as a styrene-isoprene block copolymer as the base polymer, are widely used due to their excellent adhesiveness, durability and the like.
[0003] Meanwhile, in recent years, as global awareness of environmental issues has grown, there has been an increasing demand for adhesives that do not use, or at least reduce the use of, petroleum-derived raw materials that contribute to global warming, and that use raw materials derived from biomass resources such as plants.
[0004] Therefore, Patent Document 1 discloses an adhesive composition and an adhesive sheet that include a (meth)acrylic copolymer containing 30% by mass to 95% by mass of structural units derived from (meth)acrylic acid alkyl ester monomers having a biomass degree of 70% or more, based on the total structural units, a tackifier resin, and a crosslinking agent.
[0005] Moreover, Patent Document 2 discloses a hot melt adhesive containing a thermoplastic block copolymer and a natural resin having a biomass content of 50% or more. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2022-123782 A [Patent Document 2] JP 2022-187888 A Summary of the Invention [Problem to be solved by the invention]
[0007] However, although the adhesive of Patent Document 1 has good removability, because it is an acrylic adhesive having long-chain alkyl groups on the side chains, it has insufficient adhesion to the adherend, and there is a problem of peeling in applications where strong adhesion is required.
[0008] Furthermore, the pressure-sensitive adhesive of Patent Document 2 has a low content of natural resin, making it difficult to achieve both a high biomass content and adhesive performance as an adhesive.
[0009] Therefore, an embodiment of the present invention provides a pressure-sensitive adhesive that has a high biomass ratio of 60% or more, is excellent in adhesive strength, cohesive strength (holding strength) and curved surface, and is further suitable for bonding adhesive surfaces together. [Means for solving the problem]
[0010] The present inventors have conducted intensive research to solve the above problems and have completed the present invention. That is, the present invention relates to the following embodiments. However, the present invention is not limited to the embodiments described below and includes various embodiments.
[0011] The present invention relates to a pressure-sensitive adhesive having a biomass degree of 60% or more, comprising a thermoplastic block copolymer (X) and a tackifier resin (Y), wherein the thermoplastic block copolymer (X) is a copolymer of a monovinyl aromatic hydrocarbon and a conjugated diene compound, and the tackifier resin (Y) comprises a rosin-based resin (Y1) having fluidity at 23°C and a resin (Y2) having no fluidity at 23°C.
[0012] The present invention also relates to the pressure-sensitive adhesive, wherein the thermoplastic block copolymer (X) is a styrene-based block copolymer having a diblock ratio of 40 mass% or less and a styrene content of 12 to 35 mass% relative to the total mass of the block copolymer (X).
[0013] The present invention also relates to the pressure-sensitive adhesive, wherein the thermoplastic block copolymer (X) comprises at least one selected from the group consisting of styrene-butadiene block copolymers and styrene-isoprene block copolymers.
[0014] The present invention also relates to the pressure-sensitive adhesive, wherein the content of the rosin-based resin (Y1) having fluidity at 23° C. is 15 to 180 parts by mass per 100 parts by mass of the thermoplastic block copolymer (X).
[0015] The present invention also relates to the pressure-sensitive adhesive, further comprising a plasticizer (Z).
[0016] The present invention also relates to the pressure-sensitive adhesive, wherein the thermoplastic block copolymer (X) contains a styrene-butadiene block copolymer and a styrene-isoprene block copolymer.
[0017] The present invention also relates to a pressure-sensitive adhesive sheet having a pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive on a substrate.
[0018] The present invention also relates to the pressure-sensitive adhesive sheet, wherein the substrate is a substrate having a biomass degree. Effect of the Invention
[0019] According to the present invention, it is possible to provide a pressure-sensitive adhesive that uses a high proportion of biomass-derived raw materials (biomass ratio of 60% or more) and has fully satisfactory adhesive properties. It is also possible to provide a pressure-sensitive adhesive sheet using the pressure-sensitive adhesive. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] Before describing the invention, some terms are defined. The term "adhesive sheet" as used herein means a sheet having a substrate and an adhesive layer made of the adhesive of the present invention.
[0021] In this specification, a numerical range specified using "to" means that the numerical values before and after "to" are included as the lower and upper limit values of the range. Unless otherwise noted, the various components described in this specification may be used independently as one type alone or as a combination of two or more types.
[0022] In this specification, the thermoplastic block copolymer (X) may be abbreviated as block copolymer (X). In addition, the rosin-based resin (Y1) having fluidity at 23° C. may be abbreviated as rosin-based resin (Y1), and the resin (Y2) having no fluidity at 23° C. may be abbreviated as resin (Y2).
[0023] Hereinafter, the embodiments of the present invention will be described in detail. However, the following description is an example (representative example) of the embodiment of the present invention, and the present invention is not limited to the contents thereof as long as it does not depart from the gist of the present invention.
[0024] <1> Adhesive The pressure-sensitive adhesive according to one embodiment of the present invention is a pressure-sensitive adhesive containing a thermoplastic block copolymer (X) and a tackifier resin (Y) and having a biomass ratio of 60% or more.
[0025] In the present invention, the "biomass degree" of the adhesive is calculated by calculating the biomass degree of each component constituting the adhesive, and then calculating the biomass degree of the entire adhesive from the mass ratio of each component. The biomass degree of each component is the value published by the manufacturer.
[0026] <Block copolymer (X)> The block copolymer (X) is a thermoplastic block copolymer which is a copolymer of a monovinyl aromatic hydrocarbon and a conjugated diene compound. The pressure-sensitive adhesive of the present invention can exhibit sufficient adhesive properties by including the block copolymer (X).
[0027] In the present invention, the term "block copolymer of a monovinyl-substituted aromatic compound and a conjugated diene compound" refers to a block polymer having at least one segment (hereinafter also referred to as "segment A") made of a polymer containing 50% by mass or more of a monovinyl-substituted aromatic compound and at least one segment (hereinafter also referred to as "segment B") made of a polymer containing 50% by mass or more of a conjugated diene compound. Representative structures of block copolymers include a triblock copolymer (ABA structure) having a segment A at each end of a segment B, and a diblock copolymer (AB structure) made of one segment A and one segment B. In general, the glass transition temperature of segment A is higher than that of segment B, and segment A is called a hard segment and segment B is called a soft segment.
[0028] The monovinyl-substituted aromatic compound refers to a compound in which one functional group having a vinyl group is bonded to an aromatic ring. A representative example of the aromatic ring is a benzene ring. Specific examples of the monovinyl-substituted aromatic compound include styrene, α-methylstyrene, vinyltoluene, vinylxylene, etc., and can be used alone or in combination of two or more kinds. Styrene and α-methylstyrene are preferred in terms of heat resistance.
[0029] Specific examples of the conjugated diene compound include 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, 1,3-pentadiene, 1,3-hexadiene, etc., which can be used alone or in combination of two or more. 1,3-butadiene and isoprene are preferred in that they have excellent solubility in organic solvents when used in a solvent-based pressure-sensitive adhesive and also exhibit high adhesive strength.
[0030] The segment A (hard segment) in the block copolymer (X) is The content of the monovinyl-substituted aromatic compound in 100% by mass of the monomers constituting segment A is preferably 70% by mass or more, more preferably 90% by mass or more, and may be substantially 100% by mass. Segment B (soft segment) in the block copolymer is the content of the conjugated diene compound in 100% by mass of the monomers constituting segment B. The content is preferably 70% by mass or more, more preferably 90% by mass or more, and may be substantially 100% by mass. By using such a block copolymer (X), a pressure-sensitive adhesive sheet with higher performance can be realized.
[0031] The block copolymer (X) may be a diblock, triblock, radial L) bodies, mixtures thereof, etc. In triblock and radial bodies, it is preferable that segment A is arranged at the end of the polymer chain. Segment A arranged at the end of the polymer chain is likely to gather and form a hard domain, which forms a pseudo-crosslinked structure and improves the cohesive strength (holding power) of the adhesive. On the other hand, diblock bodies have improved wettability due to the high mobility of segment B.
[0032] The block copolymer (X) in the present invention preferably has a diblock ratio of 40 mass% or less based on the total mass of the block copolymer (X). By keeping the diblock ratio within the above range, the cohesive strength (holding strength) can be maintained. The block copolymer (X) in the present invention is preferably a styrene-based block copolymer having at least one styrene block as a hard segment, and the styrene content (St content) is preferably from 12 to 35 mass %. The "styrene content" of a styrene-based block copolymer refers to the mass ratio of the styrene component to the total mass of the block copolymer. The styrene content is more preferably 15 to 31% by mass. By setting the styrene content within the above range, it becomes easy to achieve both adhesive strength and cohesive strength (holding strength). The styrene content can be confirmed from the manufacturer's catalog value.
[0033] Examples of styrene-based block copolymers include styrene-isoprene-styrene block copolymers (also referred to as "SIS"), styrene-butadiene-styrene block copolymers (also referred to as "SBS"), hydrogenated styrene-isoprene-styrene block copolymers (also referred to as "SEPS"), and hydrogenated styrene-butadiene-styrene block copolymers (also referred to as "SEBS"). Among these, it is preferable to contain at least one selected from the group consisting of SIS and SBS. It is more preferable to contain SIS, and even more preferable to contain SIS and SBS. By containing at least one selected from the group consisting of SIS and SBS, it is possible to increase the adhesive strength.
[0034] The use of two or more types of styrene block copolymers in combination can improve compatibility with the tackifier resin (Y) and provide high adhesive performance. Among these, the combination of SBS and SIS can achieve a high degree of both adhesive strength and retention.
[0035] <Tackifier resin (Y)> The tackifier resin (Y) contains a rosin-based resin (Y1) that has fluidity at 23° C. and a resin (Y2) that does not have fluidity at 23° C. By containing a rosin-based resin (Y1) that has fluidity at 23° C. and a resin (Y2) that does not have fluidity at 23° C., it is possible to exhibit excellent adhesive properties while having a high biomass content.
[0036] As a rosin-based resin (Y1) having fluidity at 23°C, for example, SYLVALITE Examples include RE12, SYLVALITE RE25, SYLVALITE 2038, SYLVALITE RE5S (all manufactured by Kraton Corporation), Forarin 5020F (manufactured by Eastman Chemical Company), and KE-364C (manufactured by Arakawa Chemical Industry Co., Ltd.) Since the rosin-based resin (Y1) that has fluidity at 23°C has a low softening point, the inclusion of such a resin gives the adhesive tack, thereby improving adhesion to the adherend.
[0037] The softening point of the rosin-based resin (Y1) having fluidity at 23°C is preferably 40°C or lower. It is also not necessary for the resin to have a softening point. If the rosin-based resin (Y1) has a softening point of 40°C or lower or does not have a softening point, it can impart sufficient tack to the adhesive. The softening point is defined as a value measured based on the softening point test method (ring and ball method) specified in JIS K 5902.
[0038] The content of the rosin-based resin (Y1) having fluidity at 23° C. in the pressure-sensitive adhesive of the present invention is preferably 15 to 180 parts by mass relative to 100 parts by mass of the block copolymer (X). The amount of the rosin resin (Y1) is more preferably 20 parts by mass or more, and even more preferably 40 parts by mass or more. Also, the amount is more preferably 150 parts by mass or less, and even more preferably 130 parts by mass or less. By making the amount of the rosin resin (Y1) 15 parts by mass or more, it is possible to impart tack to the pressure-sensitive adhesive, and by making the amount 180 parts by mass or less, it is possible to ensure cohesive strength (holding strength).
[0039] Resin (Y2) that does not have fluidity at 23° C. refers to a tackifier resin that is solid at 23° C. Examples include rosin-based resins, terpene-based resins, and petroleum-based resins, among which rosin-based resins and terpene-based resins are preferred because they can increase the biomass content. By including resin (Y2), the adhesive can have improved adhesion to the adherend, and can increase adhesive strength and curvature.
[0040] Examples of rosin-based resins that do not have fluidity at 23° C. include rosin esters obtained by esterifying unmodified rosins such as gum rosin, tall oil rosin, and wood rosin with alcohol, modified rosins such as disproportionated rosins obtained by modifying unmodified rosins, polymerized rosin, and hydrogenated rosin, modified rosin esters such as disproportionated rosin esters obtained by further esterifying these modified rosins with alcohol, polymerized rosin esters, and hydrogenated rosin esters, and rosin phenols obtained by adding phenol to unmodified rosin. Examples of such resins include Pine Crystal KE-359, Super Ester A-75, Super Ester A-100, and Pencel D-125 (all manufactured by Arakawa Chemical Industry Co., Ltd.), SYLVALITE RE80HP, SYLVALITE 85GB, and SYLVALITE RE105L (all manufactured by Kraton Corporation), and Foralin 85E and Foralin 110 (all manufactured by Eastman Chemical Company).
[0041] Terpene resins that have no fluidity at 23°C include polyterpene resins, terpene phenol resins, and hydrogenated terpene resins, such as YS Resin PX1000, YS Resin PX1250, YS Polystar T115, YS Polystar T130, Clearon P105 (all manufactured by Yasuhara Chemical Co., Ltd.), SYLVARES TR105, and SYLVARES TP2040 (all manufactured by Kraton Corporation).
[0042] Petroleum-based resins that have no fluidity at 23°C include C9 petroleum resins and C5 / C9 petroleum resins, such as Arcon P-90, Arcon P-100, Arcon P-125, Arcon M-115, Arcon M-135 (all manufactured by Arakawa Chemical Industries, Ltd.), Imave S-100, Imave S-110, Imave P-100 (all manufactured by Idemitsu Kosan Co., Ltd.), and the like.
[0043] The softening point of the resin (Y2) that does not have fluidity at 23° C. is preferably 80° C. or higher, more preferably 100° C. or higher, and is preferably 160° C. or lower, and even more preferably 140° C. or lower. When the softening point of the resin (Y2) is 80° C. or higher, the cohesive strength (holding force) can be ensured, and when it is 160° C. or lower, the adhesive strength can be improved.
[0044] The content of the resin (Y2) that does not have fluidity at 23°C in the pressure-sensitive adhesive of the present invention is preferably 60 parts by mass or more, more preferably 80 parts by mass or more, relative to 100 parts by mass of the block copolymer (X). Also, it is preferably 220 parts by mass or less, more preferably 200 parts by mass or less. When the amount of the resin (Y2) is 60 parts by mass or more, the adhesive strength can be improved, and when it is 220 parts by mass or less, tack can be secured and the adhesion to the adherend can be improved.
[0045] The total content of the rosin-based resin (Y1) having fluidity at 23° C. and the resin (Y2) having no fluidity at 23° C. in the pressure-sensitive adhesive of the present invention is preferably 170 parts by mass or more, more preferably 180 parts by mass or more, based on 100 parts by mass of the block copolymer (X). Also, it is preferably 320 parts by mass or less, more preferably 300 parts by mass or less. When the total content of the fat (Y2) is 170 parts by mass or more, the adhesive strength can be improved while increasing the biomass degree, and when it is 320 parts by mass or less, the cohesive strength (holding force) can be ensured.
[0046] The content of the rosin-based resin (Y1) having fluidity at 23° C. in the pressure-sensitive adhesive of the present invention is V Y1 The content of the resin (Y2) that does not have fluidity at 23°C is V Y2 In this case, V Y1 / V Y 2 is preferably 0.05 or more, more preferably 0.2 or more, and is preferably 1.7 or less, more preferably 1.5 or less. Y1 / V Y2 If the value is 0.05 or more, the adhesive Tack can be imparted, and by setting it to 1.7 or less, cohesive strength (holding force) can be ensured.
[0047] The adhesive of the present invention may further contain a plasticizer (Z). By containing the plasticizer (Z), the adhesive strength may be further improved. Examples of the plasticizer (Z) include monoesters, diesters, triesters of monobasic acids or polybasic acids having 1 to 18 carbon atoms and monofunctional alcohols having 1 to 18 carbon atoms, esters of unsaturated fatty acids or branched acids having 14 to 18 carbon atoms and di- to tetrahydric alcohols, esters of monobasic acids or polybasic acids having 1 to 18 carbon atoms and polyalkylene glycols, diesters, triesters, and tetraesters of hydroxy acids and monobasic acids or alcohols, fatty acid esters in which the unsaturated sites are epoxidized with peroxides or the like, phosphoric acid esters, paraffinic oils, naphthenic oils, and aromatic oils. Among these, esters of hydroxy acids and monobasic acids or alcohols, paraffinic oils, and naphthenic oils are preferred, and paraffinic oils are particularly preferred.
[0048] Examples of esters of monobasic acids or polybasic acids having 1 to 18 carbon atoms and monofunctional alcohols having 1 to 18 carbon atoms include 2-ethylhexyl oleate, isostearyl palmitate, isopropyl myristate, isostearyl laurate, dibutyl sebacate, diisodecyl adipate, tri(2-ethylhexyl) trimellitate, dimethyl phthalate, Examples include dibutyl phthalate and di(2-ethylhexyl) phthalate.
[0049] The unsaturated fatty acid having 14 to 18 carbon atoms and the di- to tetrahydric alcohol constituting the ester of the unsaturated fatty acid or branched acid having 14 to 18 carbon atoms and the di- to tetrahydric alcohol are as follows: Examples of the unsaturated fatty acid or branched acid having 14 to 18 carbon atoms include myristoleic acid, oleic acid, linoleic acid, linolenic acid, isopalmitic acid, isostearic acid, etc. Examples of the difunctional to tetrafunctional alcohol include ethylene glycol, propylene glycol, glycerin, trimethylolpropane, pentaerythritol, sorbitan, etc.
[0050] Examples of esters of monobasic acids or polybasic acids having 1 to 18 carbon atoms with polyalkylene glycols include polyethylene glycol dihexylate, polyethylene glycol di-2-ethylhexylate, polyethylene glycol dilaurate, polyethylene glycol dioleate, and dipolyethylene glycol methyl ether adipate.
[0051] Examples of esters of hydroxy acids and monobasic acids or alcohols include octyldodecyl lactate, diisostearyl malate, methyl 2-hydroxymyristate, 2-ethylhexyl 12-hydroxystearate, ethyl ricinoleate, methyl acetylricinoleate, butyl acetylricinoleate, triethyl citrate, tributyl acetylcitrate, and tri(2-ethylhexyl) acetylcitrate.
[0052] Examples of fatty acid esters in which the unsaturated site is epoxidized with a peroxide or the like include epoxidized fats and oils such as epoxidized soybean oil, epoxidized linseed oil, and epoxidized cottonseed oil, and ester compounds of epoxidized compounds of unsaturated fatty acids having 8 to 18 carbon atoms and linear or branched alcohols having 1 to 6 carbon atoms.
[0053] Examples of the phosphate ester include ester compounds of phosphoric acid and linear or branched alcohols having 2 to 18 carbon atoms. Specific examples include tributyl phosphate, 2-ethylhexyl diphenyl phosphate, oleyl acid phosphate, and ethylene glycol acid phosphate.
[0054] Commercially available paraffinic oils, naphthenic oils and aromatic oils can be used, such as Diana Freshia S32, Diana Process Oil PW-90, DN Oil KP-68 and Process Oil NS100 manufactured by Idemitsu Kosan Co., Ltd., Enerper M1930 manufactured by BP Chemicals Co., Ltd., Kaydol manufactured by Crompton Co., Ltd. and Epson Corporation. Examples include Primol352.
[0055] The content of the plasticizer (Z) in the adhesive of the present invention is preferably 2 parts by mass or more, more preferably 5 parts by mass or more, based on 100 parts by mass of the copolymer (A). Also, it is preferably 40 parts by mass or less, more preferably 20 parts by mass or less. When the content of the plasticizer (Z) is 2 parts by mass or more, the adhesion between the adhesive surfaces is increased due to improved tack, and when it is 40 parts by mass or less, the cohesive force (holding force) can be ensured.
[0056] <Other ingredients> The adhesive according to one embodiment of the present invention may further contain a general curing agent, a tackifier resin other than the rosin-based resin (Y1) having fluidity at 23° C. and the resin (Y2) having no fluidity at 23° C., and additives in addition to the above components, so long as the adhesive properties and biomass degree are not significantly reduced. Examples of curing agents that can be used include isocyanate curing agents, epoxy curing agents, melamine curing agents, carbodiimide curing agents, oxazoline curing agents, and aziridine curing agents. Examples of tackifier resins that can be used include terpene resins, petroleum resins, xylene resins, and the like having fluidity at 23° C. Examples of additives that can be used include antioxidants, ultraviolet absorbers, light stabilizers, leveling agents, antistatic agents, release regulators, fillers, colorants, antiaging agents, and surfactants. Examples of antioxidants include phenol-based antioxidants, sulfur-based antioxidants, and phosphorus-based antioxidants.
[0057] The pressure-sensitive adhesive of the present invention is preferably a one-component pressure-sensitive adhesive that does not contain a curing agent. By not containing a curing agent, the block copolymers (X) do not crosslink with each other through covalent bonds, thereby making it possible to enhance the adhesion between adhesive surfaces.
[0058] <2> Adhesive sheet Another embodiment of the present invention relates to a pressure-sensitive adhesive sheet. The pressure-sensitive adhesive sheet has a pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive of the above embodiment. That is, the pressure-sensitive adhesive sheet has a substrate and a pressure-sensitive adhesive layer composed of the pressure-sensitive adhesive of the above embodiment. In one embodiment, a release sheet may be provided on the other side of the pressure-sensitive adhesive layer that is not in contact with the substrate in order to prevent adhesion of foreign matter. Usually, the pressure-sensitive adhesive layer is protected by the release sheet until immediately before use.
[0059] The substrate may be any flexible sheet or plate material and may be used without any restrictions. Examples include plastic, paper, metal foil, and laminates composed of one or more of these materials. The surface of the substrate in contact with the adhesive layer may be subjected to a simple adhesion treatment to improve adhesion. For example, dry treatment such as corona discharge treatment or wet treatment such as application of an anchor coating agent may be applied.
[0060] In one embodiment, the plastic material constituting the substrate is, for example, an ester-based resin such as polyethylene terephthalate (PET) or polyethylene naphthalate (PEN). Examples of the resin include olefin-based resins such as polyethylene (PE), polypropylene (PP) and cycloolefin polymer (COP); vinyl-based resins such as polyvinyl chloride (PVC); amide-based resins such as nylon 66; and urethane-based resins (including foams).
[0061] In one embodiment, the resin used as the raw material for the substrate preferably has a biomass content, and examples of such resins include polybutylene succinate (PBS) resins (BioPBS FZ71, FZ91, and FZ92 manufactured by PTT MCC Biochem), polylactic acid (PLA) resins (3000 to 7000 series manufactured by NaturteWorks, and L series manufactured by Total Corbion). Series, LX series, D series, etc.
[0062] Suitable methods for forming the above resin into a substrate (sheet) include extrusion molding in which a sheet extruded through a T-die using an extruder is cooled and solidified with a cast roll, and molding using an inflation molding machine.
[0063] The thickness of the substrate may generally be 10 to 300 μm. When a polyurethane sheet (including foam) is used as the substrate, the thickness of the substrate (sheet) may generally be 20 to 50,000 μm. Paper may also be used as the substrate. Examples of the substrate include plain paper, coated paper, and art paper. Metal foil may also be used as the substrate. Examples of the metal foil include aluminum foil and copper foil.
[0064] The release sheet may be a release sheet having a known structure, for example, a release sheet obtained by applying a known release treatment such as a silicone-based release agent to the surface of a sheet-like material such as plastic or paper.
[0065] The method for producing the adhesive sheet may, for example, be a method in which the adhesive of the above embodiment is applied to the surface or both sides of the substrate to form a coating layer, and then the coating layer is dried and cured as necessary to form an adhesive layer. The adhesive may be dissolved in an organic solvent and applied, or may be thermally melted and applied without a solvent. The heating and drying temperature may generally be 60 to 200°C. The thickness of the adhesive layer may generally be 1 to 200 μm.
[0066] Methods of dissolving in an organic solvent and applying include an applicator, gravure coater, die coater, lip coater, comma coater, knife coater, reverse coater, spin coater, etc., and methods of melting and applying include an applicator, gravure coater, roll coater, die coater, slit coater, etc.
[0067] In addition, as a method different from the above method, the adhesive of the above embodiment is applied to the surface of a release sheet to form a coating layer, and then the coating layer is dried and cured as necessary to form an adhesive layer, and finally a substrate is laminated to the exposed surface of the adhesive layer. In this method, when a release sheet is laminated to the adhesive layer instead of the substrate, a cast adhesive sheet having a release sheet / adhesive layer / release sheet structure is obtained. EXAMPLES
[0068] Hereinafter, the embodiment of the present invention will be described with reference to the examples. However, it goes without saying that the embodiment of the present invention is not limited to the examples. In the following, "parts" means "parts by mass" and "%" means "% by mass". The amounts of raw materials (excluding solvents) listed in the following examples and tables are calculated based on non-volatile content.
[0069] The materials shown in Table 1 are as follows: <Block copolymer (X)> D1101: KRATON D1101, SBS, St content 31%, diblock ratio 16%, Kraton (biomass content 0%) D1161: KRATON D1161, SIS, St content 15%, diblock ratio 19%, Kraton (biomass content 0%) D1124: KRATON D1124, SIS, St content 30%, diblock ratio 30%, Kraton (biomass content 0%) G1650: KRATON G1650, SEBS, St content 30%, no diblock, Kraton (biomass content 0%) D1113: KRATON D1113, SIS, St content 16%, diblock ratio 55%, Kraton (biomass content 0%) <Thermoplastic block copolymer other than block copolymer (X)> LA2140: Clarity LA2140, acrylic block copolymer, no diblock, manufactured by Kuraray (0% biomass content)
[0070] <Tackifier resin (Y)> [Rosin-based resin (Y1) that has fluidity at 23°C] SYL2038: SYLVALITE2038, softening point 37℃, manufactured by Kraton (biomass content 94%) F-5020F: Forarin 5020F, no softening point, Eastman Chemical Company (biomass content 95%) [Resin that has no fluidity at 23°C (Y2)] A-100: Super Ester A-100, softening point 100°C, manufactured by Arakawa Chemical Industries, Ltd. (biomass content 99%) T-130: YS Polyster T-130, softening point 130℃, manufactured by Yasuhara Chemical Co., Ltd. (biomass content 65%) [Tackifier resins other than rosin-based resin (Y1) having fluidity at 23°C and resin (Y2) not having fluidity at 23°C] NL: Nikanol L, a xylene resin-based tackifier resin with fluidity at 23°C, no softening point, manufactured by Fudow Co., Ltd. (biomass content 0%)
[0071] <Plasticizer (Z)> PW-90: Diana Process Oil PW-90, paraffinic oil, manufactured by Idemitsu Kosan Co., Ltd. (biomass content 0%)
[0072] In the above-mentioned raw materials, the biomass content is the mass ratio (mass%) of the raw material derived from biomass used during production, or the content based on ASTM D6866.
[0073] [Production examples of adhesives and adhesive sheets] Example 1 Toluene was added to 100 parts of KRATON D1011, 35 parts of SYLVALITE2038, and 160 parts of Super Ester A-100 to obtain a 40% non-volatile content, and the mixture was dissolved to obtain an adhesive solution. The adhesive solution prepared above was applied to a 50 μm thick polyethylene terephthalate (PET) sheet using an applicator so that the thickness after drying would be 20 μm, and the sheet was dried in a hot air oven at 100° C. for 2 minutes to produce an adhesive layer. After drying, the sheet was laminated onto a 38 μm thick peelable sheet (made of polyethylene terephthalate) to obtain an adhesive sheet.
[0074] (Examples 2 to 14, Comparative Examples 1 to 4) The materials and blending amounts (parts by mass) of Example 1 were changed as shown in Table 1, and the adhesives and adhesive sheets of Examples 2 to 14 and Comparative Examples 1 to 4 were prepared in the same manner as in Example 1. Got it.
[0075] Example 15 An adhesive sheet of Example 15 was obtained in the same manner as in Example 2, except that the 50 μm-thick PET in Example 2 was replaced with a substrate made of polylactic acid as described below. <Production of substrate made of polylactic acid> Polylactic acid (Total Corbion LX175) resin is inserted into a 30mm diameter inflatable The mixture was extruded at 180°C using a 300°C extrusion extruder (manufactured by Tosoku Seimitsu Kogyo Co., Ltd.), and then A heat treatment was performed at 110° C. for 10 minutes to obtain a film substrate with a thickness of 80 μm.
[0076] [Biomass content of adhesive] The biomass content of an adhesive is the mass ratio of the biomass-derived raw materials used in the production of the adhesive to the total mass of the adhesive, and was calculated according to the following formula (1). Note that each mass is calculated as the non-volatile content. Calculation formula (1): Biomass content of adhesive (mass%) = 100 x [mass of biomass-derived raw materials (g)] / [total mass of adhesive (g)]
[0077] [Evaluation of adhesive sheet properties] Measurement samples were prepared according to the following methods and various physical properties were evaluated for the pressure-sensitive adhesive sheets produced using the pressure-sensitive adhesives obtained in Examples 1 to 15 and Comparative Examples 1 to 4. The results are shown in Table 1.
[0078] (1) Adhesion to SUS The obtained adhesive sheet was cut into a size of 25 mm wide and 150 mm long. Next, in an environment of 23°C and 50% relative humidity (50% RH), the release sheet was peeled off from the adhesive sheet, and the exposed adhesive layer was attached to a stainless steel (SUS) plate and rolled back and forth once with a 2 kg roll to prepare a measurement sample. After storing this measurement sample in an environment of 23°C and 50% RH for 24 hours, the peel strength was measured using a tensile tester (Orientec Co., Ltd.'s "Tensilon") at a peel speed of 300 mm / min and a peel angle of 180°. Evaluation was based on the following criteria. Evaluation criteria AA: Peel strength is 25N / 25mm or more (excellent) A: Peel strength is 20N / 25mm or more and less than 25N / 25mm (good) B: Peel strength is 15N / 25mm or more and less than 20N / 25mm (usable) C: Peel strength is less than 15N / 25mm (not suitable for use)
[0079] (2)PP adhesive strength The obtained adhesive sheet was cut into a size of 25 mm wide and 150 mm long. Next, in an environment of 23°C and 50% relative humidity (50% RH), the release sheet was peeled off from the adhesive sheet, and the exposed adhesive layer was attached to a polypropylene (PP) plate and rolled back and forth once with a 2 kg roll to prepare a measurement sample. After storing this measurement sample in an environment of 23°C and 50% RH for 24 hours, the peel strength was measured using a tensile tester (Orientec Co., Ltd.'s "Tensilon") at a peel speed of 300 mm / min and a peel angle of 180°. Evaluation was based on the following criteria. Evaluation criteria AA: Peel strength is 20N / 25mm or more (excellent) A: Peel strength is 15N / 25mm or more and less than 20N / 25mm (good) B: Peel strength is 10N / 25mm or more and less than 15N / 25mm (usable) C: Peel strength is less than 10N / 25mm (not suitable for use)
[0080] (3) Self-adhesive surface adhesive strength Two sheets of the obtained adhesive sheet were prepared, and the release sheet was peeled off from one adhesive sheet in an environment of 23°C, 50% RH, and the adhesive surface exposed by peeling off the release sheet from the other adhesive sheet was laminated on the adhesive surface exposed by peeling off the release sheet from the other adhesive sheet. The laminated adhesive sheets were then cut into a size of 25 mm wide and 150 mm long, and rolled back and forth once with a 2 kg roll to prepare a measurement sample. After storing this measurement sample in an environment of 23°C, 50% RH for 24 hours, the T-type peel strength between the laminated adhesive sheets was measured at a peel speed of 300 mm / min using a tensile tester (Orientec Co., Ltd.'s "Tensilon"). Evaluation was based on the following criteria. Evaluation criteria AA: Peel strength is 20N / 25mm or more (excellent) A: Peel strength is 15N / 25mm or more and less than 20N / 25mm (good) B: Peel strength is 10N / 25mm or more and less than 15N / 25mm (usable) C: Peel strength is less than 10N / 25mm (not suitable for use)
[0081] (4) 40℃ holding power The obtained adhesive sheet was cut into a size of 25 mm wide and 150 mm long. The release sheet was peeled off from the cut adhesive sheet, and the exposed adhesive layer was attached to a 25 mm wide and 25 mm long portion of the lower end of a 30 mm wide and 150 mm long SUS plate, and a measurement sample was made by rolling it back and forth once with a 2 kg roll. After storing this measurement sample in a 40°C environment for 20 minutes, a load was applied to the lower end of the adhesive sheet using a 1 kg weight, and the holding power was measured by leaving it for 70,000 seconds. The evaluation was performed by measuring the length by which the upper end of the adhesive surface of the adhesive sheet shifted downward from its original position. Evaluation criteria A: No deviation or deviation length is less than 0.5 mm (good) B: The deviation is between 0.5 mm and 3.0 mm (usable) C: The deviation is 3.0 mm or more (unusable)
[0082] (5)70℃ holding power The obtained adhesive sheet was cut into a size of 25 mm wide and 150 mm long. The release sheet was peeled off from the cut adhesive sheet to expose the adhesive layer, which was attached to a 25 mm wide and 25 mm long portion of the lower end of a 30 mm wide and 150 mm long SUS plate, and rolled back and forth once with a 2 kg roll to prepare a measurement sample. After storing this measurement sample in a 70°C environment for 20 minutes, a 1 kg weight was applied to the lower end of the adhesive sheet to measure the holding power. The evaluation was performed by measuring the time until the adhesive sheet and the weight fell off the SUS plate. Evaluation criteria A: No fall even after 10,000 seconds or more (good) B: Time to fall is between 1,000 and 10,000 seconds (usable) C: Time to fall is less than 1,000 seconds (not available)
[0083] (6) Curved surface The obtained adhesive sheet was cut into a size of 15 mm wide and 25 mm long. The release sheet was peeled off from the cut adhesive sheet, and the exposed adhesive layer was attached to a polypropylene (PP) rod with a diameter of 10 mm in the length direction of the adhesive sheet parallel to the circumferential direction to prepare a measurement sample. This measurement sample was stored in a 23°C environment for 20 minutes, and then kept in a 40°C environment for 24 hours. The evaluation was performed by measuring the length of peeling of the end of the adhesive surface of the adhesive sheet. Evaluation criteria A: No peeling or peeling length is less than 0.5 mm (good) B: Peeling length is 0.5 mm or more and less than 1.0 mm (usable) C: Peeling length is 1.0 mm or more (unusable)
[0084] [Table 1]
[0085] As shown in Table 1, the adhesive of the present invention (Example) contains a specific block copolymer (X), a rosin-based resin (Y1) that has fluidity at 23°C, and a resin (Y2) that does not have fluidity at 23°C. As a result, it was confirmed that the adhesive has a high biomass content and satisfies the required adhesive properties.
[0086] On the other hand, it was difficult to obtain the desired adhesive properties with the adhesives of the comparative examples. Comparative Example 1 and Comparative Example 2 do not use either the rosin-based resin (Y1) having fluidity at 23° C. or the resin (Y2) having no fluidity at 23° C. Comparative Example 3 does not use either the rosin-based resin (Y1) having fluidity at 23° C. or the resin (Y2) having no fluidity at 23° C. Comparative Example 4 does not use the thermoplastic block copolymer (X). From the above, it can be seen that the adhesive of the present invention can achieve the desired adhesive properties by using a specific block copolymer (X), a rosin-based resin (Y1) that has fluidity at 23°C, and a resin (Y2) that does not have fluidity at 23°C.
Claims
1. A pressure-sensitive adhesive having a biomass degree of 60% or more, comprising a thermoplastic block copolymer (X) and a tackifier resin (Y), wherein the thermoplastic block copolymer (X) is a copolymer of a monovinyl aromatic hydrocarbon and a conjugated diene compound, and the tackifier resin (Y) comprises a rosin-based resin (Y1) having fluidity at 23°C and a resin (Y2) having no fluidity at 23°C.
2. The pressure-sensitive adhesive according to claim 1, wherein the thermoplastic block copolymer (X) is a styrene-based block copolymer having a diblock ratio of 40 mass% or less and a styrene content of 12 to 35 mass% based on the total mass of the block copolymer (X).
3. The pressure-sensitive adhesive according to claim 1, wherein the thermoplastic block copolymer (X) comprises at least one selected from the group consisting of styrene-butadiene block copolymers and styrene-isoprene block copolymers.
4. The pressure-sensitive adhesive according to claim 1, characterized in that the content of the rosin-based resin (Y1) having fluidity at 23°C is 15 to 180 parts by mass per 100 parts by mass of the thermoplastic block copolymer (X).
5. The pressure-sensitive adhesive according to claim 1, further comprising a plasticizer (Z).
6. The pressure-sensitive adhesive according to claim 1, wherein the thermoplastic block copolymer (X) comprises a styrene-butadiene block copolymer and a styrene-isoprene block copolymer.
7. A pressure-sensitive adhesive sheet having a pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive according to any one of claims 1 to 6 on a substrate.
8. The pressure-sensitive adhesive sheet according to claim 7 , wherein the substrate is a substrate having a biomass content.
Citation Information
Patent Citations
Adhesive composition and adhesive sheet
JP2022123782A
Hot-melt adhesive
JP2022187888A